Multidimensional and comparative study on intellectual capital and organisational performance - Urban, Boris; Joubert, Gabriël Coenraad Daniël Stoltz (Journal of Business Economics and Management, 2017)
Intellectual capital (IC) as the knowledge‐based equity of organizations is increasingly recognised as an important value contributor to performance. By building on previous research, the study examines the IC components of human capital, structural capital and relational capital as they relate to organisational performance. Following past international studies, a model is developed and statistically tested. A survey is administered to firms across several industries and data is analysed employing structural equation modelling. Recognising that replications and extensions of IC studies are vital to knowledge development, comparisons with international studies are made. The results provide support for the hypotheses where relationships between the IC components and performance are evident. These findings suggest that it is crucial for an organisation to optimise the utilisation of its human capital for the sake of optimising its structural capital, which leads to higher performance. By positioning the study in terms of IC literature, the study offers the ability to compare the present study findings with similar findings across countries.